2018
DOI: 10.3389/fimmu.2018.01593
|View full text |Cite
|
Sign up to set email alerts
|

CD38 Is Robustly Induced in Human Macrophages and Monocytes in Inflammatory Conditions

Abstract: Macrophages and their monocyte precursors mediate innate immune responses and can promote a spectrum of phenotypes from pro-inflammatory to pro-resolving. Currently, there are few markers that allow for robust dissection of macrophage phenotype. We recently identified CD38 as a marker of inflammatory macrophages in murine in vitro and in vivo models. However, it is unknown whether CD38 plays a similar marker and/or functional role in human macrophages and inflammatory diseases. Here, we establish that CD38 tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
161
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(172 citation statements)
references
References 78 publications
(83 reference statements)
11
161
0
Order By: Relevance
“…Therefore, genetics can add a second dimension to the linear continuum of the macrophage polarization model. The expression of M1-associated genes such as STAT1 (FC = 1.62, FDR = 0.002), IRF1 (FC = 2.44, FDR = 2.83e-11), HIF-1A (FC = 1.44, FDR = 0.046), IL8 (FC = 2.2, FDR = 1.48e-4), CCL5 (FC = 5.83, FDR = 0.04), iNOS (FC = 2.26, FDR = 1.89e-4), CD38 (FC = 1.91, FDR = 0.023) and CD14 (FC = 1.60, FDR = 0.005) were found to be significantly more expressed in this high responder group [22][23][24]55,56 LGMN (FC = −2.86, FDR = 1.14e-9) are more expressed in low NO − responders 18,[57][58][59][60] . It should also be noted that the expression of GATA3 and IRF4, known M2-associated TFs 23 , were predicted to be inhibited in the high responder group (or activated in low responder group) based on DE genes at 18 hours (Supplementary Table 4).…”
Section: Discussionmentioning
confidence: 73%
“…Therefore, genetics can add a second dimension to the linear continuum of the macrophage polarization model. The expression of M1-associated genes such as STAT1 (FC = 1.62, FDR = 0.002), IRF1 (FC = 2.44, FDR = 2.83e-11), HIF-1A (FC = 1.44, FDR = 0.046), IL8 (FC = 2.2, FDR = 1.48e-4), CCL5 (FC = 5.83, FDR = 0.04), iNOS (FC = 2.26, FDR = 1.89e-4), CD38 (FC = 1.91, FDR = 0.023) and CD14 (FC = 1.60, FDR = 0.005) were found to be significantly more expressed in this high responder group [22][23][24]55,56 LGMN (FC = −2.86, FDR = 1.14e-9) are more expressed in low NO − responders 18,[57][58][59][60] . It should also be noted that the expression of GATA3 and IRF4, known M2-associated TFs 23 , were predicted to be inhibited in the high responder group (or activated in low responder group) based on DE genes at 18 hours (Supplementary Table 4).…”
Section: Discussionmentioning
confidence: 73%
“…We observed a corresponding pattern in the protein levels by CyTOF: in monocytes, HLA-DR protein levels decreased to a greater extent than in the other cell types ( p < 1x10 -61 for monocytes in early, mid, and late stages, rank-sum test, Figure 4B ), with a more modest reduction of HLA-DR in B cells at DPI 5-8 ( p = 0.0012, rank-sum test) ( Figure S6C ). This phenomenon held true for each individual NHP; even as monocytes became activated, demonstrated by up-regulation of the canonical activation marker CD38 (Amici et al, 2018) ( Figures 4C and S3D ), they showed dramatic down-regulation of average HLA-DR protein expression in monocytes at DPI 5-8 versus baseline ( p = 9.5x10 -7 , rank-sum test) ( Figure 4D ).…”
Section: Monocytes Express Reduced Mhc Class II Mrnas and Proteins Inmentioning
confidence: 69%
“…In our expanded multivariate analysis, we selected another set of proteins that were independently and significantly associated with higher risk of mobility loss among those that were nominally associated with mobility loss in pairwise analyses. This set included proteins that have been associated with the senescent pro‐inflammatory phenotype (MMP3, MMP13) (Roeb, 2018; Yan, 2015) and proteins biomarkers that have been associated with inflammation (NPPB, BCAM, TPO, CD38, FGR, SIGLEC1, CHST15, MAPK13; Amici et al, 2018; Munthe‐Fog et al, 2012; O'Neill, Berg, & Mullen, 2013; Tribulatti, Carabelli, Prato, & Campetella, 2019). These findings raise the idea that cellular senescence and inflammation play a role in the disablement process.…”
Section: Discussionmentioning
confidence: 99%